Antiproliferative and Pro-Apoptotic Effects of a Phenolic-Rich Extract from Lycium barbarum Fruits on Human Papillomavirus (HPV) 16-Positive Head Cancer Cell Lines - Alberto Peraza-Labrador; Diana Marcela Buitrago; Ericsson Coy-Barrera; Sandra J. Perdomo-Lara (Molecules, 2022)
The in vitro antiproliferative activity of a phenolic-rich extract from Lycium barbarum fruits against head and neck HPV16 squamous cell carcinoma (OSCC) has been demonstrated, indicating for the first time that L. barbarum extract inhibits human papillomavirus (HPV) type 16 cell lines. Ethanol extract of L. barbarum was used for cell viability evaluation on SCC090, CAL27, and HGnF cell lines. After 24 and 48 h, the cell cycle effect of L. barbarum extract (at 1.0, 10, and 100 µg/mL) was measured via flow cytometry. In addition, the mRNA expression on E6/E7 and p53 via RT-PCR and the expression of p16, p53, Ki-67, and Bcl-2 via immunohistochemistry were also determined. Untreated cells, 20 µM cisplatin, and a Camellia sinensis-derived extract were used as negative and positive controls, respectively. We demonstrated that the studied L. barbarum extract resulted in G0/G1 arrest and S phase accumulation in SCC090 at 1.0 and 10 μg/mL. A reduction in mRNA levels of E6/E7 oncogenes (p < 0.05) with p53 overexpression was also observed through PCR, while immunohistochemical analyses indicated p16 overexpression (p > 0.05) and a decrease in p53 overexpression. The observed effects were associated with anticancer and immunomodulatory phenolics, such as flavonols/flavan-3-ols and tyramine-conjugated hydroxycinnamic acid amides, identified in the studied extract. These findings revealed that the phenolic-rich extract of L. barbarum fruits has promising properties to be considered further for developing new therapies against oral and oropharyngeal HPV lesions.